Experiencing Differentiated Instructions as the Effort of Promoting Reading Comprehension Level - Taufik, Taufik (ELLITE, 2016)
The current study explored the usefulness of differentiated instruction in the promotion of English learners reading comprehension in higher educational system. One TOEFL preparation class of a language center at University of Muhammadiyah Jember was chosen as the research participants. The students were taught through the strategies of differentiated instruction, viz. flexible grouping, tiered instruction, and tiered assignments, in the areas of content, process, and product. The outcomes of descriptive statistics from comparing pre-test and post-test results indicated that the students were having a positive experience with differentiated instruction in relation to their reading comprehension level. Further, the results also revealed that students also performed better in literal and inferential reading comprehension after experiencing differentiated instruction in the classroom.Keywords: differentiated instruction, reading comprehension.